Penguatan Kesadaran Hukum Lingkungan Warga Sekitar Kawasan Danau Beratan: Penelitian - Bagus Gede Ari Rama; Dewa Krisna Prasada; Ni Putu Sawitri Nandari; Kadek Julia Mahadewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Lake Beratan in Bedugul, Bali, faces the threat of pollution due to environmentally unfriendly tourism and agricultural activities. This community service program aims to raise environmental legal awareness among local residents through legal education and advocacy. The program was conducted in three stages: observing the lake's condition and resident behavior, developing environmental law outreach materials, and implementing activities such as outreach, discussions, and waste management practices. The results showed a significant increase in residents' legal understanding; more than 80% of participants understood their rights and obligations and began implementing environmentally friendly behaviors such as sorting waste and reducing chemical use. These changes reflect the application of the concepts of Environmental Compliance, the precautionary principle, and sustainable development, where residents consciously maintain environmental sustainability based on legal, moral, and social understanding. This program emphasizes the importance of environmental legal education and advocacy as an effective strategy for building legal awareness and social responsibility to preserve Lake Beratan as a sustainable natural and cultural heritage.